The effect of two different herbicides on the weed flora in soybean - Samardzic, Natasa (Acta herbologica, 2024)
This study aimed to determine the weed species diversity in the soybean crop at two localities in the Republic of Serbia and assess the efficacy of bentazone and imazamox. Results demonstrated high to satisfactory efficacy of the both studied herbicides in the control of a variety of broadleaf weeds, as well as the grassy weeds in case of imazamox, with slight variations in the efficacy observed among the specific weed species. No phytotoxic effects were observed, while the studied herbicides had the same efficacy as the standards. It is recommended to combine these herbicides in a tank-mix in order to broaden the spectrum of the weed control and mitigate resistance issues, given their different modes of action.